The Effect of the Make A Match Cooperative Model Assisted by Matching Cards on the Mathematics Learning Outcomes of Fourth Grade Elementary School Students - Andini Putri Oktaviana; Frida Destini; Sowiyah (Journal of Adaptive Education, 2025)
The problem in this study is the low mathematics learning outcomes of fourth grade students at SD Negeri 2 Panjang Utara. This study aims to determine the effect of the Make a Match cooperative learning model assisted by matching cards on mathematics learning outcomes, as well as the difference between this model and the STAD cooperative model. The method used was quasi-experimental with a quantitative approach and saturated sampling technique involving 61 students. Data were collected through observation, interviews, documentation, and tests, and analyzed using simple linear regression. The results showed that the Make a Match model assisted by matching cards had an effect on mathematics learning outcomes. The STAD model also had an effect on mathematics learning outcomes. In addition, there were differences between the two learning models. Thus, the Make a Match model assisted by matching cards was more effective in improving mathematics learning outcomes than the STAD model.